Profil Pengendalian Diabetes Melitus Tipe 2 Di Poliklinik Penyakit Dalam RSUD Arifin Achmad Pekanbaru - Lesi Kurnia Putri; Jazil Karimi; Dimas Pramita Nugraha (Fakultas Kedokteran Universitas Riau, 2014)
Management in patients with type 2 diabetes mellitus (DM) is aimed diabetic control required antidiabetic drugs(OAD). The aim of this study was to know data about the profile of diabetics control in patients with type 2 diabetesmellitus followed in department of endocrinology Arifin Achmad General Hospital Pekanbaru. The type of researchwas descriptive. The samples are 96 people included all patients with type 2 DM according to inclusion criteria. Theidentity patients and patients knowledge were determined using questionnaire, used of antidiabetics drugs and diabeticcontrol were detemined using medical record. The characteristics of patients with type 2 DM were most at group ofage 50-59 years (45,8%), female sex (58,3%), duration of DM 1-5 years (52,1%), complication of diabetic neuropathy(25%) and frequency of the Doctor once a month (64,6%). The used OAD predominant oral antidiabetic drugs (83%)combinations sulfonylureas and biguanid (73,7%), combinations oral antidiabetic drugs with insulin (14%) arecombinations biguanid with long acting insulin (69,2%) and intensive insulin (3%) are long acting insulin with rapidacting insulin (66,6%). Diabetic control of patients with type 2 DM are fasting blood glucose, post prandial 2 hoursblood glucose, total cholesterol, LDL and HDL was bad (68%, 74%, 46,9%, 61,5% and 70,8%). This researchshowed that used of antidiabetic drugs was not satisfactory of diabetic control.